Предмет: Алгебра,
автор: казанова15
Решить уравнение
(х-3)^3(х-2)(8-2х)
Ответы
Автор ответа:
0
(x - 3)^3 * (x - 2) * (8 - 2x) = 0
(x - 3)^3 = 0
x - 3 = 0
x = 3
x - 2 = 0
x = 2
8 - 2x = 0
- 2x = - 8
x = 4
Ответ:
2 ; 3; 4
(x - 3)^3 = 0
x - 3 = 0
x = 3
x - 2 = 0
x = 2
8 - 2x = 0
- 2x = - 8
x = 4
Ответ:
2 ; 3; 4
Похожие вопросы
Предмет: Английский язык,
автор: масяня155
Предмет: Английский язык,
автор: mary1591233
Предмет: Русский язык,
автор: Аноним
Предмет: История,
автор: eldesbaev1980
Предмет: Математика,
автор: vvsvgsg